Study of shear for steel fibre reinforced concrete beam with ratio 0.2%, 0.4%, 0.6%, 0.8% and 1.0% - Ummi Izni, Mohamad Tarmizi (2010)
Concrete is the most widely used man-made construction material in the world. It can be defined as a composite material composed of a coarse granular material (the aggregate or filler) embedded in a hard matrix of material (the cement or binder) that fills the space between the particles and glues them together. One of the applications of beam is used as a floor, such as for factories and parking lot. One layer of steel fabric mesh was introduced on top or bottom section of concrete for controlling the cracks only. But during the service life, these structures are subjected to cyclic, impact loads and loads from heavy goods and etc, causing the service life of structures become shorten. These floors need an adequate fatigue flexural strength and energy absorption capacity. The application of steel fibres as an alternative way can be introduced into the beam to overcome the problem of cracking for the structure of building. This report presents an experimental study on the steel fibre reinforced concrete beams with different ratios of steel fibre. The study is about using a steel fibre as one of the component in the concrete. In this experiment, a total of eighteen reinforced concrete beam casted and tested to fail. The beam with reinforcement bar R6 and incorporated with 0.2%, 0.4%, 0.6%, 0.8%, 1.0% of steel fiber and a normal reinforced concrete beam. All the beams have overall size of 100mm x 100mm x 500mm and tested with flexural test. Experimental results on the flexural behaviour indicated that the beam with steel fiber performed almost in a same manner with the normal reinforced concrete beam. Both ultimate load capacity and flexural behaviour of steel fibre reinforced concrete were found to be higher compared to normal concrete beam. From the research, it is found that sample incorporated with 0.6% of steel fibre possessed the high compression and flexural strength compared to the other five types of samples.